THE IMPACT OF ATTITUDES TOWARDS M-LEARNING ON M-LEARNING ADOPTION: THE CASE OF THE PUBLIC UNIVERSITIES IN SAUDI ARABIA - Alblowi, Mansour Saleh (IJRDO- Journal of Educational Research, 2019)
The current study attempted to examine the relationship between attitudes towards m-learning and m-learning adoption in the higher educational context, specifically in the Saudi public universities. 381 lecturers who teach various subjects in these universities have constituted the sample of this study. The study employed a quantitative research design where a questionnaire was used as the tool for data collection which was analysed using the Statistical Package for Social Sciences (SPSS). The findings of the study revealed that the construct of attitudes was positively and significantly related to m-learning adoption. The study concluded with a number of recommendations that could be implemented by educators and policy makers in Saudi Arabia.